Wear analysis and simulation of small module gear based on Archard model. (February 2023) - Sun, Yuantao; Li, Yingcheng; Zhang, Qing; Qin, Xianrong; Chen, Kaige
Highlights: Theoretical derivation and numerical analysis of micro gear tooth surface wear based on Archard wear calculation method. The tooth profile is reconstructed by azimuth feature deviation modeling and Hertz contact theory. Tooth surface contact analysis of small module gear considering position tolerance and installation error. Solution of contact trajectory, stress and wear. Abstract: With the development of micro machining technology, small module gears are widely used in the field of high precision technology. In view of the failure problems such as tooth fracture and fatigue pitting caused by dynamic wear in the process of small module gear transmission, this paper takes a micro planetary gear reducer as the research object and establishes the analysis framework of small module gear wear calculation model based on Archard wear model and Hertz contact theory. Considering the influence of installation error and position tolerance, tooth contact analysis (TCA) model of small module gear is established based on the theory of small displacement torsor (SDT) and space coordinate transformation, and the impact of these errors on the dynamic contact trajectory, contact stress, and tooth surface wear is analyzed based on the numerical simulation. The numerical simulation results show that with the increase of the installation error, the contact trajectory will deviate significantly, which will finally result in increased contact stress and wear. Moreover, with the decrease of tolerance level, the service life of the device increases under the same reliability level. The above analysis of tooth surface wear can provide references for the design and installation of a small module gear transmission.